Transitional Dynamics and Economic Growth in the Neoclassical Model - King, Robert G.; Rebelo, Sergio T. (American Economic Review, 1993)
Neoclassical transitional dynamics are a central element of standard macroeconomic theory. Quantitative experiments with the fixed-savings-rate models of the 1960's showed lengthy transitions, thus potentially rationalizing sustained differences in growth rates across countries. We investigate quantitative transitional dynamics in various neoclassical models with intertemporally optimizing households. Lengthy transitions occur only with very low intertemporal substitution. Generally, when one tries to explain sustained economic growth with transitional dynamics, there are extremely counterfactual implications. These result from the fact that implied marginal products are extraordinarily high in the early stages of development.